PENGARUH MODEL PEMBELAJARAN TREFFINGER TERHADAP KEMAMPUAN BERPIKIR KREATIF DENGAN MENGONTROL ADVERSITY QUOTIENT - Ni Wayan Sunita (Widyadari : Jurnal Pendidikan, 2020)
The purpose of this study was to determine differences in creative thinking skills between students who took the Treffinger learning model and students who took conventional learning models by controlling the adversity quotient of semester V students of mathematics education study program FPMIPA IKIP PGRI Bali in the 2019/2020 Academic Year.This type of research used is quasi-experimental (Quasi Experimental) with Non Equivalent Control Group Design. The population in this study were all fifth semester students from 2 classes of 26 students. Obtained as a sample class is the VA class as an experimental group and VB class as a control group, with simple random sampling technique. The instrument used in this study was a questionnaire to collect adversity quotient data and a description test to collect data on students' creative thinking abilities. Data analysis used t-test and one-way covariance analysis (ANAKOVA). The results showed that: 1) the first hypothesis with the t-test that there were differences in the ability to think creatively between students who took the treffinger learning model and students who followed the conventional learning model, 2) the second hypothesis with ANAKOVA one way that there were differences creative thinking skills between students who take treffinger learning models with students who follow conventional learning models after controlling adversity quotient, so it can be concluded there is an influence of treffinger learning models on creative thinking abilities by controlling adversity quotient of semester V students of mathematics education study program FPMIPA IKIP PGRI Bali.